2014
DOI: 10.9790/3021-041203025028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bleaching on Some Quality Attributes of Crude Palm Oil

Abstract: Oil bleaching is usually done to improve colour, remove impurities and improve taste. The effect of bleaching on some quality attributes of crude palm oil was investigated. Crude palm oil was obtained from a local oil processing mill in Ika North East LGA, of Delta State Nigeria. The crude palm oil sample was divided into sample A, B and C. Sample A was unbleached, while sample B and C were bleached with heat only and bleached using Activated Coconut Pod Ash (ACPA) respectively. The physical and nutritional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Some oils may contain colored compounds that are not desired by the consumer; therefore, they should be bleached to improve their color (Mukasa-Tebandeke et al, 2014). The color improvement is due to the removal of organic compounds such as carotenoids, particularly β-carotene and their derivatives, xanthophylls, chlorophylls, pheophytins, tocopherols, gossypol, and their degradation products; these can all transmit an undesirable color to oil (Dkolo & Adejumo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some oils may contain colored compounds that are not desired by the consumer; therefore, they should be bleached to improve their color (Mukasa-Tebandeke et al, 2014). The color improvement is due to the removal of organic compounds such as carotenoids, particularly β-carotene and their derivatives, xanthophylls, chlorophylls, pheophytins, tocopherols, gossypol, and their degradation products; these can all transmit an undesirable color to oil (Dkolo & Adejumo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the effect of BE-SiO2 addition on bleaching process effectiveness, the concentration of BE-SiO2 was varied from 0% to 1.3% (w/v). The bleaching process aims to reduce the β-carotene in CPO, which affects the color of palm oil [19]. As depicted in Figure 4, the addition of more BE-SiO2 during the bleaching process enhances the adsorption of β-carotene.…”
Section: Effect Of Be-sio2 Concentrationmentioning
confidence: 99%
“…In contrast to bleaching earth Types B and C, the use of bleaching earth Type A resulted in MO kernel oil with the highest acid value and moisture content. The presence of moisture in crude oil induces hydrolysis of triglycerides, which further leads to the formation of free fatty acids, and therefore higher acid value [30,31]. Sánchez-Machado et al [9] reported a slightly different result in which the bleached MO kernel oil exhibited significantly lower PV yet higher p-AV as compared to its crude counterpart.…”
Section: Bleachingmentioning
confidence: 99%